Die australische Landwirtschaft zwischen klimatischer und marktwirtschaftlicher Herausforderung - Das Beispiel Neusüdwales - Jaschke, Dieter (ERDKUNDE, 1980)
Agricultural activities in Australia are limited by the rapidly decreasing precipitation towards the inner parts of the continent. Furthermore, the variability of precipitation is continuously menacing the economic success of both agricultural and pastoral industries. The dependence on foreign trade seriously exposes Australian agriculture to the fluctuations of prices and market conditions in the world market. Public support should help to relieve the negative influence of climate and foreign markets to such an extent that the damage done to the economy, the landscape and the social structure is reduced to a minimum. The example of New South Wales demonstrates that, as far as climate is concerned, deficits of precipitation lead to the retraction of the 'frontier' of the different agricultural and pastoral activities. The expansion of farm land and pastures generally is the outcome of influences exercised by foreign trade. It depends on the mood of the market whether the area of this or that product is expanded at the cost of another one. Slumps in the market are compensated by public support. On the other hand longer periods of favourable rainfall conditions alone do not promote the expansion of the area of any product. The increasing demand by the world market for agricultural and pastoral products will help to reduce the influence of the challenges of foreign trade in future. Thus the economic success of the expansion of land or the application of more intensive methods will depend on the fact of how far these measures can be taken in accordance with the ecology of the area involved.